Literature Review: Problems of Dental and Oral Health Primary School Children - Harun Achmad; Riana Noor Armedina; Tatiana Timokhina; Vitaly V. Goncharov; Rini Sitanaya; Eriska Riyanti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Elementary school children or the age group 6-12 years who are in mixed teeth, it is important in maintainingthe health of primary teeth which at this time has an important role in the development and maintenanceof permanent teeth later. The results of basic health research by the Indonesian Ministry of Health in 2018showed that 93% of children in Indonesia have oral health problems, which means only 7% do not havedental and oral health problems. Children this age really like sweet and sticky foods, and do not understandhow to maintain good oral health. This study aims to collect dental and oral health problems in elementaryschool children and how to deal with them. The design used is a literature review with criteria published from2007-2020. Based on the articles collected, there are several dental and oral health problems for elementaryschool children, both those affecting the hard tissues of the teeth and soft tissues or supporting teeth. Parentsand schools play an important role in educating children of this age to become accustomed to maintainingoral health.